Perceived ability and success: which self-efficacy measures matter? A distance learning perspective. (2nd September 2017) - Tladi, Lerato Sonia
Abstract: This paper sought to determine the effects of three self-efficacy measures on the academic attainment of students who were enrolled for the first time at the University of South Africa (Unisa) in 2015. The measures of interest were self-regulated learning efficacy, distance learning self-efficacy and computer and online technologies self-efficacy. Overall, only DLSE was found to have a significant effect on academic attainment albeit with a low effect ( r  = −.13), explaining only 1.7% of the variation in the academic achievement between successful and unsuccessful students. DLSE also explained 10% of the variation in academic achievement between successful and unsuccessful students who, although new to Unisa, were not new to higher education.